A study on the use of e-journals in the special libraries in ministry of defence (MINDEF). - Tan, Mun Kiat. (2008)
The number of e-journals has mushroomed in recent years. Many publishers have also eager to put their print journals online. This research originated with an aim to examine the possibilities of the joint subscription of e-journals by the libraries in Ministry of Defence (MINDEF).